Pengaruh Metode Index Card Match Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Di kelas IV SDN 202 Inpres Pattallassang - Muzakkir, AbdMalik; St. Fithriani Saleh; Ma'rup (Jurnal Riset Evaluasi Pendidikan, 2024)
The main problem in this research is that students are less interested in participating in mathematics learning, teachers in delivering learning still predominantly use the lecture method and rarely use media or tools, resulting in low mathematics learning outcomes. This research aims to determine the effect of the index card match method on student learning outcomes in mathematics learning in class IV SDN 202 Inpres Pattallassang. The type of research used is Pre-Experimental Design. The research design used was a one-group pretest-posttest design. The sample in this study was 20 students. Data collection techniques were carried out using observation sheets and learning outcomes tests. The data analysis technique in this research is a descriptive data analysis technique for student learning outcomes and learning activities as well as the N-Gain test. Based on data obtained from research, the research results show that: (1) the average student learning outcomes before using the index card match method was 50.75, only 3 students out of a total of 20 students or 15% in the class achieved the criteria for achieving learning objectives (KKTP). The average student learning outcome after using the index card match method was 77.25. 17 students out of a total of 20 students or 85% achieved the learning objective achievement criteria (KKTP) and had fulfilled the class completion criteria. (2) The average increase in student learning outcomes (gain) in mathematics learning is 0.562 which is in the medium category. (3) The average percentage of student activity in class IV mathematics learning at SDN 202 Inpres Pattallassang using the index card match method is 86.25% with a student activity indicator of at least 80% of students in the class actively involved during learning. So it can be concluded that the index card match method influences student learning outcomes in mathematics learning in class IV SDN 202 Inpres Pattallassang.